Dormant Ties: The Value Of Reconnecting - Levin, Daniel Z.; Walter, Jorge; Murnighan, J. Keith (Organization Science, 2011)
The social networks literature suggests that ties must be maintained to retain value. In contrast, we show that reconnecting dormant ties—former ties, now out of touch—can be extremely useful. Our research prompted Executive MBA students to consult their dormant contacts about an important work project; outcomes compared favorably to those of their current ties. In addition, reconnecting previously strong ties led to all of the four benefits that are usually associated with either weak ties (efficiency and novelty) or strong ties (trust and shared perspective). These findings suggest that dormant relationships—often overlooked or underutilized—can be a valuable source of knowledge and social capital.